Combined Knowledge And Physics Based Approaches Towards Predicting Protein Structures - Khairudin , Nurul Bahiyah Ahmad (2009)
Proteins are the building block of life. Knowledge of the three dimensional structure of proteins is of fundamental importance in understanding protein function. In this study, a new computational method was developed to predict these structures by combining the knowledge-based homology modeling and the physics-based molecular dynamics simulation methods. The core region of the protein wasinitially constructed via homology modeling based on sequence similarity with other solved protein templates. Then, the remaining end-terminal regions were allowed to fold towards the core region via MD simulation a few residues at a time. The method was categorized into three parts; the development of the core region of the protein, the development of the complete protein structure and the MD refinement simulation